1998
DOI: 10.1002/(sici)1521-4095(199802)10:3<230::aid-adma230>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Exciplex Electroluminescence from Organic Bilayer Devices Composed of Triphenyldiamine and Quinoxaline Derivatives

Abstract: Exciplexes can be used as emission sources in light‐emitting devices (LEDs), as is demonstrated here. High electroluminescence is reported from bilayer organic LEDs in which the emission is confirmed to originate from an exciplex formed at the interface of two organic layers, for example of an aromatic diamine and a quinoxaline derivative, one of which is shown in the Figure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(54 citation statements)
references
References 2 publications
0
53
0
1
Order By: Relevance
“…In addition, exciplex emission is radiative recombination of singlet CT excitons and therefore generally exhibits low efficiency. 24,25 Due to a large separation distance between the electrons and holes, CT excitons have been demonstrated recently to have a very small singlet-triplet energy splitting, which enables an efficient transition from nonradiative triplet states to radiative singlet states via a reverse-intersystem-crossing (RISC) process. 26,27 Therefore, fluorescent OLEDs based on exciplex emission can harvest both singlet and triplet excitons through prompt and delayed fluorescent decay channels.…”
Section: Exciplex Emissionmentioning
confidence: 99%
“…In addition, exciplex emission is radiative recombination of singlet CT excitons and therefore generally exhibits low efficiency. 24,25 Due to a large separation distance between the electrons and holes, CT excitons have been demonstrated recently to have a very small singlet-triplet energy splitting, which enables an efficient transition from nonradiative triplet states to radiative singlet states via a reverse-intersystem-crossing (RISC) process. 26,27 Therefore, fluorescent OLEDs based on exciplex emission can harvest both singlet and triplet excitons through prompt and delayed fluorescent decay channels.…”
Section: Exciplex Emissionmentioning
confidence: 99%
“…Recently, a number of papers appeared showing EL spectra of OLEDs to differ substantially from the photoluminescence (PL) spectra of their component materials [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Often, EL spectra show up as red-shifted broad bands that have been mostly assigned as emission from exciplexes formed at the solid interface between a hole-transport layer (HTL) and an electron-transport layer (ETL).…”
Section: Introductionmentioning
confidence: 99%
“…[410][411] Quinoxalines are very important compounds due to their wide spectrum of biological activities such as anticancer, [412][413] antibacterial 414 and activity as kinase inhibitors. 415 It was reported that the Kaupp and co-workers (Scheme 122).…”
Section: Quinoxalinesmentioning
confidence: 99%